التكامل المعرفي بين النظرية والتطبيق في إندونيسيا - Mohammad Syairozi Dimyathi; Hannanah Mukhtar Thabrani (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The developments that took place in the sciences in Islam throughout its history were not without a clash or an epistemological, ontological and axiological conflict between the religious sciences and the general sciences. This conflict has led to a kind of duality or antagonism between the religious sciences and the general sciences, or between the sciences of this world and the sciences of the afterlife, so to speak. There is an integrated perspective of science and knowledge that includes all its types and all its sections, which benefit a man to continue his life in the world and the hereafter, in his present and future, in his condition and his destiny, in the matter and beyond matter. This research attempts to answer the most important models of cognitive integration among Muslim thinkers, and how to apply scientific and cognitive integration at Syarif Hidayatullah State Islamic University (UIN) Jakarta as a model. To answer these questions, the analytical deductive method was used. One of the results of this research is that there are different models for the integration of religious and general sciences, whether at the global or local levels in Indonesian universities. Almost all of them agree that there is no separation between religious and general sciences, and that religious values are the spirit of those sciences in general.